PENCIPTAAN BUKU ILUSTRASI LEGEND REOG PONOROGO SEBAGAI UPAYA MENGENALKAN BUDAYA LOKAL KEPADA ANAK-ANAK - Ikawira, Erlangga Yudha (Jurnal Art Nouveau, 2014)
Abstract: Reog Ponorogo is one that is owned by the Indonesian culture that must be preserved and also introduced early to children, because they are the nations potential successor. But the local culture such as Reog start eroded by modern smelling things, like modern games, other than that the children have fear when seeing the show Reog who still uses magical elements. One of the Reog Ponorogo way to introduce children is through a book with a fun design. The purpose of this research is making legend Reog Ponorogo illustrated book based on the lack of interest in the dance Reog in modern times such as this, because in dance reog still thick with mystical elements and it collides with the modern world as it is today, and the children who will become the nations next seedlings tend to be afraid when he saw the show reog. This study used qualitative methods, through a process of interviews, literature studies, and observation. Once the data is acquired, it can be concluded that the analysis results are Reog Ponorogo need to be introduced to children from an early age, starting from knowing his legend first, so that the continuity of culture in Indonesia can be maintained. From the analysis, then obtained the key word is